2017
DOI: 10.1021/acs.macromol.7b01989
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of a High Molecular Weight Amphiphilic Aramid–ROMP Block Copolymer

Abstract: Herein we report the facile synthesis of an amphiphilic rod-coil block copolymer obtained by the coupling of an amine terminated poly(dimethylpropylamine norbornene imide) (PDMNI) and a pentafluorophenol ester terminated poly(dimethoxybenzyl paraaminobenzoate) (PAram). Post-polymerization amide N-deprotection of the block copolymer yielded a strongly aggregating water soluble rod-coil copolymer. Transmission electron microscopy revealed the formation of large ribbon-like aggregates with sizes up to 50 nanomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Hence, in the case of a BCP, signals corresponding to different blocks but correlating to the same diffusivity prove that the blocks are indeed connected. [63][64][65][66] A decrease in the diffusion coefficient in comparison with the homopolymers or macroinitiator allows for a qualitative evaluation of an increase in the molecular weight. Loo et al exploited DOSY analysis for mapping the actual molecular weight distribution.…”
Section: Alternative Methods For Molecular Weight Determinationmentioning
confidence: 99%
“…Hence, in the case of a BCP, signals corresponding to different blocks but correlating to the same diffusivity prove that the blocks are indeed connected. [63][64][65][66] A decrease in the diffusion coefficient in comparison with the homopolymers or macroinitiator allows for a qualitative evaluation of an increase in the molecular weight. Loo et al exploited DOSY analysis for mapping the actual molecular weight distribution.…”
Section: Alternative Methods For Molecular Weight Determinationmentioning
confidence: 99%
“…The spherical or rodlike micelles’ number depended on poly(ethylene glycol) length in nonpolar solvents. The schematic self-assembly behavior of the block copolymer is shown in Figure 3 A. Badoux et al [ 34 ] prepared an amphiphilic aramid–ROMP block copolymer which self-assembled into large ribbonlike aggregates up to 50 nm in thickness and 300 nm in length ( Figure 3 B). Kataoka et al [ 35 ] reported the gelation of monodisperse diblock copolymers of poly( N -octyl m -benzamide) with poly( p -benzamide) or poly( m -benzamide).…”
Section: Self-assembly Of Pptamentioning
confidence: 99%
“…Copyright 2010 American Chemical Society (Washington, DC, USA). ( B ) TEM pictures and schematic self-assembly behavior of amphiphilic aramid–ROMP block copolymer [ 34 ]. Copyright 2017 American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…On top of this, it has been demonstrated that PLA is a suitable substitute for many commodity plastics synthesized from petroleum derivatives which makes it a good target for commercial applications. PLA is industrially produced from the ROP of lactide (LA), a transformation requiring high temperatures and the intervention of an efficient catalyst. , Despite the continuous efforts to implement sustainable catalysis in its production, the current synthetic pathway requires metal catalysts, the most widespread example being tin octoate (SnOct 2 ), employed because of its excellent thermal stability and high activity even at low catalyst loading. However, the subsequent removal of SnOct 2 is arduous, which regularly compromises the applicability of PLA and generates environmental issues at the end of the useful life of the plastic when it is left to biodegrade. In addition, at the industrial level, concerns have been raised due to upcoming regulations limiting the use of tin-based catalysts …”
Section: Introductionmentioning
confidence: 99%